A PVC tape

By adding specific materials to the base layer and adhesive layer of PVC tape, its wear resistance, tensile strength and anti-aging properties are improved, and the problem of easy degumming in harsh environments of existing PVC tape is solved, achieving higher performance and service life.

CN119119885BActive Publication Date: 2025-04-25SHENZHEN WANGLITONG ELECTRONIC TECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411344713.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-04-25
Estimated Expiration
2044-09-25

AI Technical Summary

Technical Problem

Existing PVC tapes are prone to problems such as degumming, wear resistance, tensile strength and anti-aging properties in harsh environments such as long-term use and high temperature and water immersion.

Method used

By adding polypropylene fiber and glass fiber reinforced fibers to the base layer of the PVC tape, and adding high-temperature stabilizers of aluminum silicate, titanium oxide and calcium stearate to the adhesive layer, as well as silicone copolymers formed by reacting silicone resin with epoxy resin, the wear resistance, tensile strength and anti-aging properties of the tape are improved.

Benefits of technology

It significantly improves the wear resistance, tensile strength and anti-aging properties of PVC tape, making it more stable in high temperature and humidity environments and extends its service life.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a PVC tape, comprising a base layer and an adhesive layer adhered to the surface of the base layer, wherein the base layer is prepared from the following raw materials in parts by weight: 90-100 parts of PVC resin, 5-8 parts of reinforcing fiber, 1-2 parts of stabilizer, 3-5 parts of plasticizer, 8-13 parts of first filler, 0.1-0.3 parts of colorant, and 0.2-1 parts of impact modifier; the adhesive layer is prepared from the following raw materials in parts by weight: 80-100 parts of epoxy resin, 34-40 parts of curing agent, 2-3 parts of accelerator, 15-30 parts of second filler, 15-20 parts of diluent, 18-28 parts of high temperature resistant stabilizer, and 40-60 parts of silicone resin; the invention adds reinforcing fiber composed of polypropylene fiber and glass fiber to the base layer of the PVC tape, the polypropylene fiber can enhance the wear resistance of the base layer, so that the average wear resistance of the PVC tape is more than 1500 times, and the tensile strength of the base layer is enhanced by the glass fiber, so that the average tensile strength of the PVC tape is more than 50MPa.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of PVC tapes, in particular to a PVC tape. Background Art

[0002] PVC tape refers to a strip product made by coating adhesive on PVC film. PVC insulation tape has been widely used due to its advantages such as low price, waterproof, flame retardant, color separation, etc. It is suitable for the insulation of various resistor parts, such as wire joint winding, insulation damage repair, transformer, motor, capacitor, voltage stabilizer and other types of motor and electronic parts insulation protection. It can also be used for bundling, fixing, overlapping, repairing, sealing and protection in industrial processes. The existing PVC tape is made of polyvinyl chloride film as the base material and coated with rubber-type pressure-sensitive adhesive. However, since the adhesion when the glue is directly applied to the PVC base material is not strong enough, debonding will still occur after long-term bonding and repeated bending, which seriously affects the use effect. At present, the average tensile strength of PVC tape is 35MPa, the average bonding strength is 10N / cm, the average wear resistance is 1000 times, and the average anti-aging performance is 1000 hours. For the high performance requirements of PVC tape, its performance can no longer meet the use requirements, and PVC tape may be used in harsh environments such as high temperature and water immersion. In order to overcome the above shortcomings, it is necessary to design a new type of PVC tape based on the shortcomings of the prior art. Summary of the invention

[0003] In view of the deficiencies of the prior art, the object of the present invention is to provide a PVC tape, which has good wear resistance, strong tensile strength, and improved heat resistance and water resistance.

[0004] In order to solve the above technical problems, the present invention provides a PVC tape, characterized in that it includes a base layer and an adhesive layer adhered to the surface of the base layer, and the base layer is prepared from the following raw materials in parts by weight:

[0005] 90-100 parts of PVC resin, 5-8 parts of reinforcing fiber, 1-2 parts of stabilizer, 3-5 parts of plasticizer, 8-13 parts of first filler, 0.1-0.3 parts of colorant, 0.2-1 parts of impact modifier;

[0006] The adhesive layer is prepared from the following raw materials in parts by weight:

[0007] 80-100 parts of epoxy resin, 34-40 parts of curing agent, 2-3 parts of accelerator, 15-30 parts of second filler, 15-20 parts of diluent, 18-28 parts of high temperature stabilizer, 40-60 parts of silicone resin;

[0008] The mass ratio of the epoxy resin to the silicone resin is (2-3): (1-1.8).

[0009] As a preferred solution of the present invention, the reinforcing fibers are formed by interweaving and twisting polypropylene fibers and glass fibers, and the mass ratio of the polypropylene fibers to the glass fibers is (2.5-4): (1-1.5).

[0010] As a preferred solution of the present invention, the stabilizer is calcium stearate, the plasticizer is one or more of phthalate and polyadipate; the first filler is calcium carbonate; the colorant is titanium dioxide; and the impact modifier is methyl methacrylate-butadiene-styrene copolymer.

[0011] As a preferred solution of the present invention, the epoxy resin and the silicone resin are reacted by dealcoholization to form a siloxane copolymer.

[0012] As a preferred embodiment of the present invention, the preparation method of the siloxane copolymer is:

[0013] S1. Dissolving epoxy resin: adding epoxy resin and polar solvent into a container, and heating to an appropriate temperature so that the epoxy resin is completely dissolved in the selected solvent to form a uniform epoxy resin solution;

[0014] S2. Adding silicone resin: adding a specified amount of silicone resin to the epoxy resin solution, stirring evenly, and ensuring that the two are fully mixed to form a mixed solution;

[0015] S3. Heating reaction: The mixed solution is transferred to a reaction container, heated to the required reaction temperature, and a dealcoholization reaction is carried out under the action of a catalyst. The alkoxy groups in the silicone resin react with the hydroxyl groups in the epoxy resin to remove small alcohol molecules and form a stable silicon-oxygen-alkane bond.

[0016] As a preferred solution of the present invention, the high temperature resistant stabilizer is a mixture of aluminum silicate, titanium dioxide and calcium stearate, wherein the mass ratio of aluminum silicate, titanium dioxide and calcium stearate is 1: (2-2.5): (1.5-2).

[0017] As a preferred embodiment of the present invention, the curing agent is one or more of amino acid, diethylenetriamine, triethylenetetramine, polyethylenepolyamine, tetraethylenepentamine, polyamide resin, and dodecenylsuccinic anhydride; the accelerator is one or more of DMP-30, triethylamine, triethanolamine, BMDA, DBU, DMP-10, pyridine, and diethyltetramethylimidazole; and the diluent is acetone.

[0018] As a preferred solution of the present invention, the second filler is one of iron oxide powder, iron powder, aluminum powder, zinc powder, white carbon black, wollastonite powder and alumina.

[0019] As a preferred solution of the present invention, the base layer is prepared from the following raw materials in parts by weight:

[0020] 96 parts of PVC resin, 7 parts of reinforcing fiber, 1.5 parts of stabilizer, 4 parts of plasticizer, 10 parts of first filler, 0.2 parts of colorant, 0.6 parts of impact modifier;

[0021] The adhesive layer is prepared from the following raw materials in parts by weight:

[0022] 90 parts of epoxy resin, 37 parts of curing agent, 2.5 parts of accelerator, 25 parts of second filler, 18 parts of diluent, 23 parts of high temperature stabilizer, 50 parts of silicone resin;

[0023] The mass ratio of the epoxy resin to the silicone resin is 2.3:1.5.

[0024] As a preferred solution of the present invention, the mass ratio of the polypropylene fiber to the glass fiber is 3.4:1.3.

[0025] As a preferred embodiment of the present invention, the mass ratio of aluminum silicate, titanium dioxide and calcium stearate is 1:2.2:1.7.

[0026] Compared with the prior art, the present invention has the following beneficial effects:

[0027] The present invention adds reinforcing fibers composed of polypropylene fibers and glass fibers to the base layer of the PVC tape. The polypropylene fibers can enhance the wear resistance of the base layer, so that the average wear resistance of the PVC tape is more than 1500 times. The glass fibers enhance the tensile strength of the base layer, so that the average tensile strength of the PVC tape is more than 50 MPa. Calcium carbonate is added to the PVC tape to play a skeleton role, which helps to enhance the dimensional stability of the tape. At the same time, the addition of calcium carbonate can also improve the rigidity of the PVC tape, making it more stiff and less prone to deformation during use. A plasticizer is added and a UV protection layer is provided on the outer side of the base layer to resist the erosion and aging of UV rays. While ensuring the flexibility of the tape, its anti-aging performance is improved. A high temperature resistant stabilizer composed of aluminum silicate, titanium dioxide and calcium stearate is added to the composite layer. Aluminum silicate has high high temperature stability and can maintain its excellent performance in a high temperature environment. Aluminum silicate has a low thermal conductivity and has excellent thermal insulation performance. Titanium dioxide can significantly improve the thermal stability of the PVC tape and reduce degradation and aging in a high temperature environment. Calcium stearate exhibits good light and heat stabilization in the PVC tape and can prevent degradation and aging due to light and heat during processing and use, thereby improving the heat resistance of the PVC tape. By adding an organic silicone resin to react with an epoxy resin to form a siloxane copolymer, the PVC tape has excellent water resistance. By adding a second filler as a reinforcing filler, the curing shrinkage force can be reduced and the bonding strength can be improved. DETAILED DESCRIPTION

[0028] To make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be described in detail below. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other implementation methods obtained by ordinary technicians in this field without creative work belong to the scope of protection of the present invention.

[0029] The specific raw materials mentioned in the following examples can all be obtained commercially, and the techniques and equipment used are well known to those skilled in the art.

[0030] The present invention provides a technical solution:

[0031] A PVC tape comprises a base layer and an adhesive layer adhered to the surface of the base layer, wherein the base layer is prepared from the following raw materials in parts by weight:

[0032] 90-100 parts of PVC resin, 5-8 parts of reinforcing fiber, 1-2 parts of stabilizer, 3-5 parts of plasticizer, 8-13 parts of first filler, 0.1-0.3 parts of colorant, 0.2-1 parts of impact modifier;

[0033] In this embodiment, the reinforcing fibers are formed by interweaving and twisting polypropylene fibers and glass fibers, and the mass ratio of the polypropylene fibers to the glass fibers is (2.5-4): (1-1.5);

[0034] In this embodiment, the stabilizer is calcium stearate, the plasticizer is one or more of phthalate and polyadipate; the first filler is calcium carbonate; the colorant is titanium dioxide; the impact modifier is methyl methacrylate-butadiene-styrene copolymer;

[0035] In this embodiment, the outer side of the base layer is also coated with an ultraviolet protection layer.

[0036] The invention adds reinforcing fibers composed of polypropylene fibers and glass fibers to the base layer of the PVC adhesive tape. The polypropylene fibers can enhance the wear resistance of the base layer, so that the average wear resistance of the PVC adhesive tape is more than 1500 times. The glass fibers enhance the tensile strength of the base layer, so that the average tensile strength of the PVC adhesive tape is more than 50 MPa. Calcium carbonate is added to the PVC adhesive tape to play a skeleton role, which helps to enhance the dimensional stability of the adhesive tape. Meanwhile, the addition of calcium carbonate can also improve the rigidity of the PVC adhesive tape, so that the PVC adhesive tape is more stiff and less prone to deformation during use. A plasticizer is added and a layer of ultraviolet protection layer is provided on the outer side of the base layer to resist the erosion and aging of ultraviolet rays. The flexibility of the adhesive tape is ensured and the anti-aging performance is improved.

[0037] The adhesive layer is prepared from the following raw materials in parts by weight:

[0038] 80-100 parts of epoxy resin, 34-40 parts of curing agent, 2-3 parts of accelerator, 15-30 parts of second filler, 15-20 parts of diluent, 18-28 parts of high temperature stabilizer, 40-60 parts of silicone resin;

[0039] The mass ratio of the epoxy resin to the silicone resin (2-3): (1-1.8);

[0040] The epoxy resin and the silicone resin form a siloxane copolymer through a dealcoholization reaction;

[0041] The preparation method of the siloxane copolymer is:

[0042] S1. Dissolving epoxy resin: adding epoxy resin and polar solvent into a container, and heating to an appropriate temperature so that the epoxy resin is completely dissolved in the selected solvent to form a uniform epoxy resin solution;

[0043] S2. Adding silicone resin: adding a specified amount of silicone resin to the epoxy resin solution, stirring evenly, and ensuring that the two are fully mixed to form a mixed solution;

[0044] S3. Heating reaction: The mixed solution is transferred to a reaction container, heated to the required reaction temperature, and a dealcoholization reaction is carried out under the action of a catalyst. The alkoxy groups in the silicone resin react with the hydroxyl groups in the epoxy resin to remove small alcohol molecules and form a stable silicon-oxygen-alkane bond.

[0045] In this embodiment, the high temperature resistant stabilizer is a mixture of aluminum silicate, titanium dioxide and calcium stearate, wherein the mass ratio of aluminum silicate, titanium dioxide and calcium stearate is 1:(2-2.5):(1.5-2).

[0046] In this embodiment, the curing agent is one or more of amino acid, diethylenetriamine, triethylenetetramine, polyethylenepolyamine, tetraethylenepentamine, polyamide resin, and dodecenylsuccinic anhydride; the accelerator is one or more of DMP-30, triethylamine, triethanolamine, BMDA, DBU, DMP-10, pyridine, and diethyltetramethylimidazole; and the diluent is acetone.

[0047] In this embodiment, the second filler is one of iron oxide powder, iron powder, aluminum powder, zinc powder, white carbon black, wollastonite powder, and alumina.

[0048] The invention adds a high-temperature resistant stabilizer composed of aluminum silicate, titanium dioxide and calcium stearate to the adhesive layer of the PVC tape. The aluminum silicate has high high-temperature stability and can maintain its excellent performance under high-temperature environment. The aluminum silicate has low thermal conductivity and excellent heat insulation performance. The titanium dioxide can significantly improve the thermal stability of the PVC tape and reduce degradation and aging under high-temperature environment. The calcium stearate exhibits good light and heat stabilization in the PVC tape and can prevent degradation and aging due to light and heat during processing and use, thereby improving the heat resistance of the PVC tape. The organic silicon resin is added to react with the epoxy resin to form a siloxane copolymer, so that the PVC tape has excellent water resistance. The second filler is added as a reinforcing filler to reduce the curing shrinkage force and improve the bonding strength.

[0049] Specific implementation cases Example 1

[0050] A PVC tape comprises a base layer and an adhesive layer adhered to the surface of the base layer, wherein the base layer is prepared from the following raw materials in parts by weight:

[0051] 96 parts of PVC resin, 7 parts of reinforcing fiber, 1.5 parts of stabilizer, 4 parts of plasticizer, 10 parts of first filler, 0.2 parts of colorant, 0.6 parts of impact modifier;

[0052] The mass ratio of polypropylene fiber to glass fiber in the reinforcing fiber is 3.4:1.3;

[0053] The stabilizer is calcium stearate, the plasticizer is phthalate, the first filler is calcium carbonate, the colorant is titanium dioxide, and the impact modifier is methyl methacrylate-butadiene-styrene copolymer;

[0054] The adhesive layer is prepared from the following raw materials in parts by weight:

[0055] 90 parts of epoxy resin, 37 parts of curing agent, 2.5 parts of accelerator, 25 parts of second filler, 18 parts of diluent, 23 parts of high temperature stabilizer, 50 parts of silicone resin;

[0056] The mass ratio of the epoxy resin to the silicone resin is 2.3:1.5, and the epoxy resin and the silicone resin form a siloxane copolymer through a dealcoholization reaction;

[0057] The preparation method of the siloxane copolymer is:

[0058] S1. Dissolving epoxy resin: adding 2.3 parts by mass of epoxy resin and polar solvent into a container, and heating to an appropriate temperature so that the epoxy resin is completely dissolved in the selected solvent to form a uniform epoxy resin solution;

[0059] S2, adding silicone resin: adding 1.5 parts by mass of silicone resin to the epoxy resin solution, stirring evenly to ensure that the two are fully mixed to form a mixed solution;

[0060] S3, temperature-raising reaction: the mixed solution is transferred to a reaction container, the temperature is raised to the required reaction temperature, and a dealcoholization reaction is carried out under the action of a catalyst, the alkoxy groups in the silicone resin react with the hydroxyl groups in the epoxy resin, the alcohol small molecules are removed, and a stable silicon-oxygen-alkane bond is formed;

[0061] The mass ratio of aluminum silicate, titanium dioxide and calcium stearate in the high temperature resistant stabilizer is 1:2.2:1.7;

[0062] The curing agent is amino acid, the accelerator is triethanolamine, the diluent is acetone, and the second filler is aluminum oxide.

[0063] The preparation method of the PVC tape is:

[0064] The base material is added into a mixer and mixed evenly, and then sent into an extruder to be extruded into a film to obtain a base layer;

[0065] The adhesive layer raw materials are added into a mixer and mixed evenly to obtain an adhesive, and then the adhesive is coated on the base layer to form an adhesive layer, thereby obtaining the PVC tape.

[0066] Example 2

[0067] A PVC tape comprises a base layer and an adhesive layer adhered to the surface of the base layer, wherein the base layer is prepared from the following raw materials in parts by weight:

[0068] 92 parts of PVC resin, 6 parts of reinforcing fiber, 1.3 parts of stabilizer, 3 parts of plasticizer, 8 parts of first filler, 0.1 parts of colorant, 0.3 parts of impact modifier;

[0069] The mass ratio of polypropylene fiber to glass fiber in the reinforcing fiber is 2.7:1;

[0070] The stabilizer is calcium stearate, the plasticizer is phthalate, the first filler is calcium carbonate, the colorant is titanium dioxide, and the impact modifier is methyl methacrylate-butadiene-styrene copolymer;

[0071] The adhesive layer is prepared from the following raw materials in parts by weight:

[0072] 85 parts of epoxy resin, 34 parts of curing agent, 2 parts of accelerator, 20 parts of second filler, 15 parts of diluent, 18 parts of high temperature stabilizer, 45 parts of silicone resin;

[0073] The mass ratio of the epoxy resin to the silicone resin is 2:1, and the epoxy resin and the silicone resin form a siloxane copolymer through a dealcoholization reaction;

[0074] The preparation method of the siloxane copolymer is:

[0075] S1. Dissolving epoxy resin: adding 2 parts by mass of epoxy resin and polar solvent into a container, and heating to an appropriate temperature so that the epoxy resin is completely dissolved in the selected solvent to form a uniform epoxy resin solution;

[0076] S2, adding silicone resin: adding 1 part by mass of silicone resin to the epoxy resin solution, stirring evenly to ensure that the two are fully mixed to form a mixed solution;

[0077] S3, temperature-raising reaction: the mixed solution is transferred to a reaction container, the temperature is raised to the required reaction temperature, and a dealcoholization reaction is carried out under the action of a catalyst, the alkoxy groups in the silicone resin react with the hydroxyl groups in the epoxy resin, the alcohol small molecules are removed, and a stable silicon-oxygen-alkane bond is formed;

[0078] The mass ratio of aluminum silicate, titanium dioxide and calcium stearate in the high temperature resistant stabilizer is 1:2:1.5;

[0079] The curing agent is amino acid, the accelerator is triethanolamine, the diluent is acetone, and the second filler is aluminum oxide.

[0080] The preparation method of the PVC tape is:

[0081] The base material is added into a mixer and mixed evenly, and then sent into an extruder to be extruded into a film to obtain a base layer;

[0082] The adhesive layer raw materials are added into a mixer and mixed evenly to obtain an adhesive, and then the adhesive is coated on the base layer to form an adhesive layer, thereby obtaining the PVC tape.

[0083] Example 3

[0084] 100 parts of PVC resin, 8 parts of reinforcing fiber, 2 parts of stabilizer, 4.5 parts of plasticizer, 12 parts of first filler, 0.3 parts of colorant, 0.8 parts of impact modifier;

[0085] The mass ratio of polypropylene fiber to glass fiber in the reinforcing fiber is 3.8:1.5;

[0086] The stabilizer is calcium stearate, the plasticizer is phthalate, the first filler is calcium carbonate, the colorant is titanium dioxide, and the impact modifier is methyl methacrylate-butadiene-styrene copolymer;

[0087] The adhesive layer is prepared from the following raw materials in parts by weight:

[0088] 95 parts of epoxy resin, 40 parts of curing agent, 3 parts of accelerator, 30 parts of second filler, 20 parts of diluent, 26 parts of high temperature stabilizer, 55 parts of silicone resin;

[0089] The mass ratio of the epoxy resin to the silicone resin is 2.6:1.8, and the epoxy resin and the silicone resin form a siloxane copolymer through a dealcoholization reaction;

[0090] The preparation method of the siloxane copolymer is:

[0091] S1. Dissolving epoxy resin: adding 2.6 parts by mass of epoxy resin and polar solvent into a container, and heating to an appropriate temperature so that the epoxy resin is completely dissolved in the selected solvent to form a uniform epoxy resin solution;

[0092] S2, adding silicone resin: adding 1.8 parts by mass of silicone resin to the epoxy resin solution, stirring evenly to ensure that the two are fully mixed to form a mixed solution;

[0093] S3, temperature-raising reaction: the mixed solution is transferred to a reaction container, the temperature is raised to the required reaction temperature, and a dealcoholization reaction is carried out under the action of a catalyst, the alkoxy groups in the silicone resin react with the hydroxyl groups in the epoxy resin, the alcohol small molecules are removed, and a stable silicon-oxygen-alkane bond is formed;

[0094] The mass ratio of aluminum silicate, titanium dioxide and calcium stearate in the high temperature resistant stabilizer is 1:2:1.5;

[0095] The curing agent is amino acid, the accelerator is triethanolamine, the diluent is acetone, and the second filler is aluminum oxide.

[0096] The preparation method of the PVC tape is:

[0097] The base material is added into a mixer and mixed evenly, and then sent into an extruder to be extruded into a film to obtain a base layer;

[0098] The adhesive layer raw materials are added into a mixer and mixed evenly to obtain an adhesive, and then the adhesive is coated on the base layer to form an adhesive layer, thereby obtaining the PVC tape.

[0099] Comparative Example 1

[0100] The difference between Comparative Example 1 and Example 1 is that Comparative Example 1 does not contain reinforcing fibers, and the other aspects are the same.

[0101] Comparative Example 2

[0102] The difference between Comparative Example 2 and Example 1 is that the reinforcing fiber described in Comparative Example 2 is different from that in Example 1, and the other parts are the same;

[0103] In this comparative example, the reinforcing fibers do not contain glass fibers.

[0104] Comparative Example 3

[0105] The difference between Comparative Example 3 and Example 1 is that the reinforcing fiber described in Comparative Example 3 is different from that in Example 1, and the other parts are the same;

[0106] In this comparative example, the reinforcing fibers do not contain polypropylene fibers.

[0107] Comparative Example 4

[0108] The difference between Comparative Example 4 and Example 1 is that Comparative Example 2 does not contain the second filler, and the other parts are the same.

[0109] Comparative Example 5

[0110] The difference between Comparative Example 5 and Example 1 is that Comparative Example 5 does not contain a high temperature resistant stabilizer, and the other aspects are the same.

[0111] Comparative Example 6

[0112] The difference between Comparative Example 6 and Example 1 is that the high temperature resistant stabilizer described in Comparative Example 6 is different from that in Example 1, and the others are the same;

[0113] In this comparative example, the high temperature resistant stabilizer does not contain aluminum silicate, and the other components are the same;

[0114] The high temperature resistant stabilizer is composed of titanium dioxide and calcium stearate in a weight ratio of 2:1.5.

[0115] Comparative Example 7

[0116] The difference between Comparative Example 7 and Example 1 is that the high temperature resistant stabilizer described in Comparative Example 7 is different from that in Example 1, and the others are the same;

[0117] In this comparative example, the high temperature resistant stabilizer does not contain titanium dioxide, and the other components are the same;

[0118] The high temperature resistant stabilizer is composed of aluminum silicate and calcium stearate in a weight ratio of 1:1.5.

[0119] Comparative Example 8

[0120] The difference between Comparative Example 8 and Example 1 is that the high temperature resistant stabilizer described in Comparative Example 8 is different from that in Example 1, and the others are the same;

[0121] In this comparative example, the high temperature resistant stabilizer does not contain calcium stearate, and the others are the same;

[0122] The high temperature resistant stabilizer is composed of aluminum silicate and titanium dioxide in a weight ratio of 1:2.

[0123] Comparative Example 9

[0124] The difference between Comparative Example 9 and Example 1 is that Comparative Example 4 does not contain silicone resin.

[0125] In order to further demonstrate the effect of the present invention, the following test method is provided:

[0126] The bonding strength test of the adhesive layer was carried out by peeling experiments using aluminum alloy bonding, stainless steel bonding, and glass fiber bonding. The test results are shown in Table 1:

[0127] Table 1

[0128] Aluminum alloy bonding strength (MPa) Stainless steel bonding strength (MPa) Glass fiber bonding strength (MPa) Example 1 85 80 78 Comparative Example 4 80 75 68

[0129] As can be seen from Table 1, the PVC tape of the present invention has a stronger bonding strength.

[0130] The heat resistance test of the adhesive layer was conducted by bonding aluminum alloy with adhesive and then using a heat deformation temperature tester to test the heat deformation temperature. The test results are shown in Table 2:

[0131] Table 2

[0132] Heat deformation temperature (℃) Example 1 190 Example 2 188 Example 3 187 Comparative Example 5 165 Comparative Example 6 178 Comparative Example 7 181 Comparative Example 8 177

[0133] It can be seen from Table 2 that the PVC tape of the present invention has stronger heat resistance.

[0134] The water resistance test of the adhesive layer is performed by bonding the aluminum alloy with an adhesive, and then performing a water resistance temperature test using a water resistance tester. The test results are shown in Table 3:

[0135] Table 3

[0136] Adhesion strength retention rate after 24 hours of immersion in water (%) Example 1 88 Example 2 85 Example 3 86 Comparative Example 9 75

[0137] As can be seen from Table 1, the PVC tape of the present invention has stronger water resistance.

[0138] The wear resistance and tensile strength test of the base layer, the base layer samples were tested for tensile strength using a universal material testing machine, and the wear resistance was tested using a wear resistance testing machine. The test results are shown in Table 4:

[0139] Table 4

[0140] Tensile strength (MPa) Wear times (±50) Example 1 52 1500 Example 2 46 1460 Example 3 48 1400 Comparative Example 1 35 1000 Comparative Example 2 35 1300 Comparative Example 3 44 1050

[0141] As can be seen from Table 4, the PVC tape of the present invention has stronger tensile strength and abrasion resistance.

[0142] All technical features in this embodiment can be freely combined according to actual needs.

[0143] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.

Claims

1. A PVC tape, characterized in that: It comprises a base layer and an adhesive layer adhered to the surface of the base layer, wherein the base layer is prepared from the following raw materials in parts by weight: 90-100 parts of PVC resin, 5-8 parts of reinforcing fiber, 1-2 parts of stabilizer, 3-5 parts of plasticizer, 8-13 parts of first filler, 0.1-0.3 parts of colorant, 0.2-1 parts of impact modifier; The reinforcing fibers are formed by interweaving and twisting polypropylene fibers and glass fibers, and the mass ratio of the polypropylene fibers to the glass fibers is (2.5-4): (1-1.5); The adhesive layer is prepared from the following raw materials in parts by weight: 80-100 parts of epoxy resin, 34-40 parts of curing agent, 2-3 parts of accelerator, 15-30 parts of second filler, 15-20 parts of diluent, 18-28 parts of high temperature stabilizer, 40-60 parts of silicone resin; The mass ratio of the epoxy resin to the silicone resin (2-3): (1-1.8); The high temperature resistant stabilizer is prepared by mixing aluminum silicate, titanium dioxide and calcium stearate, wherein the mass ratio of aluminum silicate, titanium dioxide and calcium stearate is 1:(2-2.5):(1.5-2).

2. A PVC tape according to claim 1, characterized in that: The stabilizer is calcium stearate, the plasticizer is one or more of phthalate and polyadipate; the first filler is calcium carbonate; the colorant is titanium dioxide; and the impact modifier is methyl methacrylate-butadiene-styrene copolymer.

3. A PVC tape according to claim 1, characterized in that: The epoxy resin and the organic silicone resin form a siloxane copolymer through a dealcoholization reaction.

4. A PVC tape according to claim 3, characterized in that: The preparation method of the siloxane copolymer is: S1. Dissolving epoxy resin: adding epoxy resin and polar solvent into a container, and heating to an appropriate temperature so that the epoxy resin is completely dissolved in the selected solvent to form a uniform epoxy resin solution; S2. Adding silicone resin: adding a specified amount of silicone resin to the epoxy resin solution, stirring evenly to ensure that the two are fully mixed to form a mixed solution; S3. Heating reaction: The mixed solution is transferred to a reaction container, heated to the required reaction temperature, and a dealcoholization reaction is carried out under the action of a catalyst. The alkoxy groups in the silicone resin react with the hydroxyl groups in the epoxy resin to remove small alcohol molecules and form a stable silicon-oxygen-alkane bond.

5. A PVC tape according to claim 1, characterized in that: The curing agent is one or more of amino acid, diethylenetriamine, triethylenetetramine, polyethylenepolyamine, tetraethylenepentamine, polyamide resin, and dodecenylsuccinic anhydride; the accelerator is one or more of DMP-30, triethylamine, triethanolamine, BMDA, DBU, DMP-10, pyridine, and diethyltetramethylimidazole; the diluent is acetone, and the second filler is one of iron oxide powder, iron powder, aluminum powder, zinc powder, white carbon black, wollastonite powder, and alumina.

6. A PVC tape according to claim 1, characterized in that: The base layer is prepared from the following raw materials in parts by weight: 96 parts of PVC resin, 7 parts of reinforcing fiber, 1.5 parts of stabilizer, 4 parts of plasticizer, 10 parts of first filler, 0.2 parts of colorant, 0.6 parts of impact modifier; The adhesive layer is prepared from the following raw materials in parts by weight: 90 parts of epoxy resin, 37 parts of curing agent, 2.5 parts of accelerator, 25 parts of second filler, 18 parts of diluent, 23 parts of high temperature stabilizer, 50 parts of silicone resin; The mass ratio of the epoxy resin to the silicone resin is 2.3:1.

5.

7. A PVC tape according to claim 6, characterized in that: The mass ratio of the polypropylene fiber to the glass fiber is 3.4:1.

3.

8. A PVC tape according to claim 6, characterized in that: The mass ratio of the aluminum silicate, titanium dioxide and calcium stearate is 1:2.2:1.7.

Citation Information

Patent Citations

  • Heat-resistant decorative film and preparation method thereof

    CN107627696A

  • High-strength wear-resistant film

    CN107804052A